Financial capacity of provinces in Sumatra during regional autonomy era - Rosmeli Rosmeli; Nurhayani Nurhayani (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
The regional autonomy policy gives greater authority to regencies and cities to take responsibilities both in terms of regional revenue or regional expenditure. Ideally, all the local government expenditures can be fulfilled with their Local Own-source Revenue, so that the region fully becomes an autonomous region which means that the dependence of central government to local decreases. According to the percentage of direct expenditure to total regional revenue of provinces in Sumatra, the average amount is less than 50 percent of regional income. Meanwhile, more than 50 percent of the total regional revenue of provinces in Sumatra is used for indirect expenditure. The average degree of fiscal decentralization of provinces in Sumatra from 2015 to 2017 has amount about 37 percent. It means that the fiscal decentralization degree was low, thus the budgeting performance was poor/bad. Financial independence level of provinces in Sumatra is 57.36 percent which means that the regions are considered to be independent enough in implementing regional autonomy. Financial dependence level of region is about 63.55 percent which means that the fiscal dependence of provinces in Sumatra is great enough and its budget performance is not so good. This shows that the region dependence in Sumatra on the aids from central funds is still very much felt and noticeable.